Revitalizing Love and Compassion Values Education at Religious Education Learning in National Curriculum in Indonesia - Sukiman, Sukiman; Suyatno, Suyatno; Yap, Siti Nursheila Khairuddin (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
Love and compassion values are taught in every religion. But the values have not been practiced in students' daily lives. This research aimed to analyze whether love and compassion values of each religion are included in the content of the religious education curriculum at schools, how the problems faced in instilling love and compassion values of love in students, and how revitalization efforts in the future. The research method used was literature research. The data collection technique was documentation. The data were analyzed using critically performed text analysis. The results showed: First, the curriculum of religious education at schools for all religions in Indonesia contained love and compassion values, although with different sequences. Second, the problem faced was that internalizing love and compassion values in students had not been realized well because of inappropriate methods. Third, the process of instilling love and compassion values in religious learning needs to be revitalized by applying more effective learning methods. Three effective methods for instilling love and compassion values in students were habituation, exemplary, and reflective learning.